2018
DOI: 10.1097/mrr.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of translation of the RAND 36-item health survey in a post-rehabilitation population

Abstract: The aim of this study is to evaluate the reliability of the RAND 36-item Health survey as a measure of health-related quality of life in a general Dutch post-rehabilitation population. A total of 752 ex-rehabilitation patients were invited to complete the Dutch RAND 36-item health survey. After 2 weeks, the people who responded to the first questionnaire were asked to complete the same questionnaire again. Internal consistency of the questionnaire was expressed as Cronbach's α. Test-retest reliability was expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…This scale consists of 10 questions with three levels of response ('yes, strongly limited', 'yes, a bit limited', and 'no, not limited'). The total score ranges from 0 to 100, with higher scores indicating better physical functioning [28,29].…”
Section: Rand-36 Physical Functioningmentioning
confidence: 99%
“…This scale consists of 10 questions with three levels of response ('yes, strongly limited', 'yes, a bit limited', and 'no, not limited'). The total score ranges from 0 to 100, with higher scores indicating better physical functioning [28,29].…”
Section: Rand-36 Physical Functioningmentioning
confidence: 99%
“…Daily PA and sedentary behaviour were measured using the Short Questionnaire to Assess Health-enhancing physical activity (SQUASH) adapted for wheelchair use [36,37]. Previous research has found the abovementioned tests and questionnaires to be reliable and valid for specific sub-populations of the physically disabled population (Supplementary File 1) [29,30,[34][35][36][38][39][40].…”
Section: Questionnairesmentioning
confidence: 99%
“…The questionnaires included to investigate eating habits were the 21-item Three-Factor Eating Questionnaire (TFEQ-R21) 20 and the Questionnaire on Eating and Weight Patterns-Revised (QEWP-R). 21 For information on physical activity and quality of life, the Saltin Grimby physical activity level questionnaire (SGQ), 22 the RAND-36 questionnaire 23 and EuroQol five-dimensional questionnaire (EQ-5D) 24 were included. The Beck Anxiety Inventory (BAI), 25 for the measurement of severity of anxiety and the Patient Health Questionnaire-9 (PHQ-9), 26 a self-reported measure of depression, were also included to investigate psychological health.…”
Section: Methodsmentioning
confidence: 99%